Nouthetic Counseling Defended: A Reply to Ganz - Carter, John D. (Journal of psychology and theology, 1976)
This paper is to reply to Ganz's critique of Carter's (1975a) analysis of Adams’ theory of Nouthetic Counseling. It begins with a further analysis of Adams’ thoughts. Several weaknesses were noted in Adams thought: omission of central biblical concepts, rejection of common grace, a theologically inadequate view of the fall, uncritically using psychological concepts yet claiming to be exclusively biblical, ignoring psychology as phenomena and a rhetoric which is confusing. Ganz's comments were then responded to in detail. At many points Ganz did not appear to understand the nature of the original analysis and reacted to a label he placed on my original analysis.